2000
DOI: 10.4269/ajtmh.2000.62.284
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid studies in children with cerebral malaria: an excitotoxic mechanism?

Abstract: Abstract. The pathogenesis of cerebral malaria is poorly understood. One hypothesis is that activation of microglia and astrocytes in the brain might cause the cerebral symptoms by excitotoxic mechanisms. Cerebrospinal fluid was sampled in 97 Kenyan children with cerebral malaria, 85% within 48 hr of admission. When compared with an agematched reference range, there were large increases in concentrations of the excitotoxin quinolinic acid (geometric mean ratio cerebral malaria/reference population [95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 65 publications
4
63
0
Order By: Relevance
“…IDO activity correlates with disease severity in chronic HIV disease (20) and cancer malignancy (21) and is associated with dysregulated immune responses and impaired microvascular reactivity in sepsis (22). Induction of the kynurenine pathway has been shown in murine (23) and falciparum (24)(25)(26) malaria, but its role in vivax malaria has yet to be investigated.…”
mentioning
confidence: 99%
“…IDO activity correlates with disease severity in chronic HIV disease (20) and cancer malignancy (21) and is associated with dysregulated immune responses and impaired microvascular reactivity in sepsis (22). Induction of the kynurenine pathway has been shown in murine (23) and falciparum (24)(25)(26) malaria, but its role in vivax malaria has yet to be investigated.…”
mentioning
confidence: 99%
“…One study of Zambian children with CM revealed that low total biopterin (biopterin, dihydrobiopterin, and tetrahydrobiopterin) in cerebral spinal fluid correlated with deep coma (22). Another study in coastal Kenya reported elevated tetrahydrobiopterin levels in subjects with CM that were more than 10 times higher than those measured in Zambian children (5). The discrepant results highlight the difficulties in measuring biopterin metabolites in biologic fluids (10), especially in clinical studies of malaria in developing countries (11).…”
mentioning
confidence: 99%
“…We show that treatment of infected mice with a kynurenine-3-hydroxylase inhibitor prevents them from developing neurological symptoms and extends their life span threefold until severe anemia develops.One possible cause of death associated with cerebral malaria is an imbalance in the production of neurotoxic and neuroprotective factors brought about by parasite-triggered cerebral inflammation (7,13,14). A candidate mechanism in this process is the kynurenine pathway from tryptophan, which is activated in macrophages and microglia by inflammatory stimuli and which generates excitotoxic and neuroprotectant metabolites (1, 8).…”
mentioning
confidence: 99%